Perancangan Sistem Pendukung Keputusan Berbasis Rekayasa Perangkat Lunak Membantu Penentuan Prioritas Penanganan Perkara Hukum - Irianto; Abdul Karim Syahputra; Sumantri (Management of Information System Journal, 2026)
The increasing number of legal cases requiring resolution has created significant challenges for law enforcement agencies in determining case handling priorities in an objective, timely, and consistent manner. This study aims to design a Software Engineering-based Decision Support System (DSS) to assist in determining the priority of legal case handling based on predefined evaluation criteria. The Simple Additive Weighting (SAW) method is employed to perform the weighting and ranking of case alternatives, while the software development process follows the Waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance. The evaluation criteria include case urgency, social impact, number of victims, case complexity, and case resolution deadlines. System evaluation is conducted through functional testing using Black Box Testing, software quality assessment based on the ISO/IEC 25010 quality characteristics (functional suitability, usability, and performance efficiency), and recommendation accuracy measurement by comparing the system-generated rankings with expert judgments using the Spearman Rank Correlation coefficient. The expected system performance targets include 100% functional success, a minimum usability score of 85% (excellent category), a system response time of less than 3 seconds, and a ranking correlation coefficient of ≥0.90, indicating a very high level of agreement between the system recommendations and expert decisions. The expected outcome of this research is a Decision Support System capable of improving objectivity, consistency, and efficiency in prioritizing legal case handling while reducing subjectivity in the decision-making process.